Resimen Para Komando Angkatan Darat (RPKAD) dalam operasi militer di Indonesia 1959-1966 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The main problem examined in this thesis is how the Regiments of the Army Commands in Military Operations in Indonesia in 1959-1966. The research method used is a historical method consisting of four steps, namely heuristics, source criticism, interpretation and historiography. Based on the research findings, it was found that Indonesian special forces were formed due to the need for military operations in the context of eradicating the rampant rebellion movement after Indonesia’s independence, Indonesia did not yet have a force that had special abilities. Then from those needs a special force was formed. In the development of special forces organizations there have been several reorganizations to perfect special forces and also special forces organizations. At first the special forces organization was called the Army Command Unit, the Army Command Regiment until now called KOPASSUS. After perfecting the organization and special forces in 1959 until 1966 Indonesian special forces had carried out various military and non-war military operations such as: Dwikora Operations wishing to return West Irian to Indonesia, Operation Trikora Confrontation that occurred between Indonesia and Indonesia Malaysia, and the September 30/PKI Movement suppression operation that wanted to make Indonesia a Communist country
Keywords: Indonesian Special Forces; Military Operation; PKAD